2018
DOI: 10.1108/ijopm-05-2017-0306
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain learning of sustainability in multi-tier supply chains

Abstract: The aim of the paper is to explore how multinational corporations (MNCs) orchestrate internal and external resources to help their multi-tier supply chains learn sustainability related knowledge. Design/methodology/approach-An exploratory multiple case study approach was adopted and three MNCs' sustainable initiatives in China were examined. The data were primarily collected through 43 semi-structured interviews with managers of focal companies and their multi-tier suppliers. Findings-We found that in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
302
0
21

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(339 citation statements)
references
References 65 publications
16
302
0
21
Order By: Relevance
“…For example, from the resource orchestration viewpoint, Sirmon et al (2007) emphasized the role of firms' internal capabilities in structuring, bundling, and leveraging the resources portfolio. Wales et al (2013), Teece (2014), and Gong, Jia, Brown, and Koh (2018) indicated that resources should be orchestrated. A study by Chadwick et al (2015) also highlighted the role of firms in orchestrating resources.…”
Section: Introductionmentioning
confidence: 99%
“…For example, from the resource orchestration viewpoint, Sirmon et al (2007) emphasized the role of firms' internal capabilities in structuring, bundling, and leveraging the resources portfolio. Wales et al (2013), Teece (2014), and Gong, Jia, Brown, and Koh (2018) indicated that resources should be orchestrated. A study by Chadwick et al (2015) also highlighted the role of firms in orchestrating resources.…”
Section: Introductionmentioning
confidence: 99%
“…Because green innovation requires more interactions with external stakeholders, firms need to learn from their suppliers and customers to obtain information, resources, and knowledge (Chen & Hung, 2014;De Marchi, 2012;Noci & Verganti, 1999;Zhu, Sarkis, & Lai, 2013). Thus, the paradigm of green innovation has shifted from a solo model to a supply chain learning model (Chiou et al, 2011;Dangelico & Pujari, 2010;Gong, Jia, Brown, & Koh, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Supply chain learning refers to activities that a firm looks both upstream and downstream of its supply chain to manage and monitor the internal and external learning processes (Flint, Larsson, & Gammelgaard, 2008;Hernández-Espallardo, Rodríguez-Orejuela, & Sánchez-Pérez, 2010). Although the importance of supply chain learning has been recognized (Gong et al, 2018;Willis, Genchev, & Chen, 2016), our understanding of how and under what conditions it impact on green innovation is still limited. Thus, two research questions can be extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging, which includes mobilizing, coordinating, and deploying, aims to make use of capabilities to create value. Despite the rapid development of the resource orchestration perspective, the relevant research is still in its infancy and is dispersed across the different fields of entrepreneurship (Baert et al, ; Chao, Coombs, Qian, & Sirmon, ; Wales, Patel, Parida, & Kreiser, ; Wang, Liang, Zhong, Xue, & Xiao, ), innovation (Carnes, Chirico, Hitt, Dong, & Pisano, ), supply chain management (Gong, Jia, Brown, & Koh, ; Hitt, Xu, & Carnes, ; Ketchen, Wowak, & Craighead, ), and IS (Cui et al, ; Cui & Pan, ; Du, Cui, & Su, ; Liu, Wei, Ke, Wei, & Hua, ; Wang et al, ; Zhou, Zhang, Chen, & Han, ). Such studies focus on either investigating the role of resource orchestration in achieving an outcome or revealing the process of resource orchestration.…”
Section: Theoretical Backgroundmentioning
confidence: 99%